2005
DOI: 10.1039/b414180f
|View full text |Cite
|
Sign up to set email alerts
|

An easily integrative and efficient micromixer and its application to the spectroscopic detection of glucose-catalyst reactions

Abstract: The focus of this paper is on the fabrication of a PDMS-based passive efficient micromixer to be easily integrated into the other on-chip microfluidic system. The mixing is achieved by "strong stretching and folding," which employs a three-dimensional microchannel structure. By the simultaneously vertical and transversal dispersion of fluids, strong advection is developed. Owing to this powerful mixing performance (more than 70% of the mixing is accomplished within 2.3 mm over a wide range of Reynold number (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Passive designs are often desirable in applications involving sensitive species (e.g., biological samples) because they do not impose strong mechanical, electrical, or thermal agitation. Examples of passive micromixing approaches that have been widely investigated include the following: (i) ''split-and-recombine'' strategies where the streams to be mixed are divided or split into multiple channels and redirected along trajectories that allow them to be subsequently reassembled as alternating lamellae yielding exponential reductions in interspecies diffusion length and time scales (4,(10)(11)(12); and (ii) ''chaotic'' strategies where transverse flows are passively generated that continuously expand interfacial area between species through stretching, folding, and breakup processes (13)(14)(15)(16)(17)(18)(19)(20). The microchannel structures associated with these mixing elements range from relatively simple topological features on one or more channel walls (ridges, grooves, or other protrusions that can, for example, be constructed by means of multiple soft lithography, alignment, and bonding steps) to intricate 3D flow networks requiring timescales on the order of days to fabricate.…”
mentioning
confidence: 99%
“…Passive designs are often desirable in applications involving sensitive species (e.g., biological samples) because they do not impose strong mechanical, electrical, or thermal agitation. Examples of passive micromixing approaches that have been widely investigated include the following: (i) ''split-and-recombine'' strategies where the streams to be mixed are divided or split into multiple channels and redirected along trajectories that allow them to be subsequently reassembled as alternating lamellae yielding exponential reductions in interspecies diffusion length and time scales (4,(10)(11)(12); and (ii) ''chaotic'' strategies where transverse flows are passively generated that continuously expand interfacial area between species through stretching, folding, and breakup processes (13)(14)(15)(16)(17)(18)(19)(20). The microchannel structures associated with these mixing elements range from relatively simple topological features on one or more channel walls (ridges, grooves, or other protrusions that can, for example, be constructed by means of multiple soft lithography, alignment, and bonding steps) to intricate 3D flow networks requiring timescales on the order of days to fabricate.…”
mentioning
confidence: 99%
“…Using this saw channel, together with a fluorescence/Raman optical detection technique, we successfully performed quantitative analyses of duplex DNA oligonucleotides, 20 cyanide pollutants in water, 18 glucosecatalyzed reactions, 21 and DNA oligomers. 11 To determine the optimal flow rate for fluorescence measurements, the flow rate was changed from 1 to 20 μL/min by regulating the microsyringe pump.…”
Section: Resultsmentioning
confidence: 99%
“…The seven rectangles denote the fluorescence measurement areas. Our previous work 20,21 demonstrated that this three-dimensional PDMS channel is very effective in mixing two laminar-flow streams when compared with a serpentine or twisted chaotic channel, because stronger advection is developed by the simultaneous vertical and transverse dispersion of the confluent streams.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high mixing efficiency of the multiphase fluids (analyte fluid, nanoparticle colloid and sometimes oil), various efficient functional microchannels have been succeeded in applications for SERS-based microsystems laminar flow mixing such as alligator teeth-shaped microfluidic channels, 60,61 zig zag-shaped microfluidic channels, 62,63 pillar array microfluidic channels, 27,31 and microdroplet microfluidic channels. 48 In the previously mentioned functional microchannels, the nanocolloids and analytes are introduced into a channel where they are mixed with each other with high efficiency.…”
Section: Micromixermentioning
confidence: 99%